The Relationship Between Pianists’ Perceptions and Spinal Posture Following Alexander Technique Lessons - Wong, Grace; Comeau, Gilles; Russell, Donald (Revue musicale OICRM, 2022)
Studies have shown that musicians feel their posture has improved after studying the Alexander Technique (at). However, no study has examined if participants’ perceptions agree with their quantitatively measured posture. This study explored the relationship between pianists’ perceptions of their posture along with their application of the Technique and the measurements taken of their spinal posture. Fifteen pianists completed questionnaires about how they perceived their posture and how they applied at principles while playing. Their responses were compared with their own postural data collected during a previous study to determine if there were commonalities between pianists’ perceptions and their postural changes. Results showed a wide range of responses as to how pianists applied the Technique while playing. Findings also showed that there was not always a clear relationship between participants’ perceptions and their postural data. In conclusion, pianists’ perceptions do not always agree with direct measures of posture.